The plays of Shakespeare : a thematic guide - Cahn, Victor L. (Greenwood Press, 2001)
Touching viewers and readers with his presentation of social, moral, and political issues, Shakespeare holds ageless and unequaled appeal primarily because of the universal themes at the heart of his dramatic works. Shakespeare scholar Victor Cahn takes a unique approach to exploring the plays by identifying and explicating the themes that recur throughout the canon. Written in lively language, each of the 35 essays explores a core theme or topic and discusses its implications in several key plays in which it figures prominently. This user-friendly guide not only allows readers to understand better the significance of concepts such as power, politics, marriage or money; the organization by theme also helps users to compare and contrast these important topics across relevant plays. Cahn draws vivid connections between related works of Shakespeare, but just as importantly, enlightens readers as to the pertinence of these themes in contemporary life. Cahn (affiliation not cited) identifies and explicates the themes that recur throughout Shakespeare's canon of 37 plays. Each of the 35 essays explores a core theme or topic and discusses its implications in several key plays in which it figures prominently. Attention is focused on the characters and how they reveal themselves through language and action. Some of the topics examined are: acting, clerics, divine right, fidelity, fools, gender, honor, language, love, male friendship, marriage, mortality, politics, reason vs. passion, revenge, the tragic flaw, and war. Identifies the core topics of Shakespeare's plays and allows students to compare and contrast the thematic connections that recur throughout the canon.